A Single Case Report of Sacral Nerve Stimulation in Neurogenic Bladder Dysfunction: A Physiotherapeutic Perspective - Dimpi Phukan; Deepjyoti Barman; Kangkan Talukdar; Ankur Jyoti Bora (International Journal of Emergency and Trauma Nursing and Practices, 2025)
Background: This case study evaluates the effectiveness of sacral nerve stimulation (SNS) for improving neurological bladder function in a 34-year-old male patient, who underwent surgical intervention at the level of L4 for Conus Medullaris Syndrome. The patient presented with severe neurological deficits including bladder dysfunction. Method: Post-surgery, a targeted physiotherapy regimen, including faradic current stimulation to the sacral nerves (S2-S4) and conventional exercises was implemented to address bladder function. Pre- and post-intervention evaluations were carried out using Manual Muscle Testing (MMT) and the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF). Result: Notable improvements were seen: MMT scores rose from 0 to 3, and ICIQ-UI SF scores decreased from 20 to 9, indicating the potential effectiveness of SNS in treating neurogenic bladder dysfunction. The p-value was 0.046, which is below 0.05, confirming that the differences in MMT and ICIQ-UI SF scores are statistically significant. Conclusion: SNS demonstrated effectiveness in improving bladder function and quality of life for the patient. These results emphasize the value of incorporating SNS into clinical practice for individuals with neurogenic bladder dysfunction.
Keywords: Sacral nerve stimulation (SNS); electrical muscle stimulator; manual muscle testing (MMT); neurogenic bladder dysfunction; pelvic floor exercises; the international consultation on incontinence questionnaire-urinary incontinence short form (ICIQ-UI SF); urinary incontinence